Effect of environmental factors on the abundance of decapod crustaceans from soft bottoms off southeastern Brazil - Furlan, Michele; Castilho, Antonio L.; Fernandes-goes, Lissandra C.; Fransozo, Vivian; Bertini, Giovana; Costa, Rogério Caetano da [UNESP] (Academia Brasileira de Ciências, 2013)
Este estudo investigou a importância dos fatores ambientais sobre os padrões de abundância dos decápodos na costa sudeste brasileira. Amostragens foram feitas mensalmente de janeiro/1998 a dezembro/1999 em Ubatumirim e Mar Virado, região de Ubatuba, usando um barco de pesca camaroneiro equipado com redes doublerig. Foram selecionadas seis áreas adjacentes aos costões rochosos. Amostras de água de fundo foram coletadas usando garrafa de Nansen, para mensurar a temperatura e salinidade. Amostras de sedimento foram obtidas utilizando pegador de Van Veen, para determinação da textura e conteúdo de matéria orgânica. A associação dos fatores ambientais com a abundância das espécies foi verificada através da Análise de Correspondência Canônica (α = 0,05). Quarenta e uma espécies de Decapoda foram utilizadas na análise multivariada. A análise indicou que a textura do sedimento (phi) e a temperatura foram os fatores mais fortemente correlacionados (p < 0,05) com a abundância espacial e temporal das espécies. Considerando a região de estudo como zona de transição faunística, incluindo espécies de origem tropical e subantártica, as espécies responderam diferentemente aos fatores ambientais, principalmente à temperatura. Possivelmente os decápodos ajustem sua distribuição de acordo com suas limitações fisiológicas intrínsecas, como resultado dos recursos disponíveis.

This study investigated the importance of variations in environmental factors affecting the abundance patterns of decapods on the southeastern Brazilian coast. Sampling was carried out monthly from January 1998 through December 1999 in Ubatumirim and Mar Virado, Ubatuba region, using a commercial shrimp fishing boat equipped with double-rig nets. Six areas adjacent to rocky shores were chosen. Bottom-water samples were collected using a Nansen bottle, to measure the temperature and salinity. Sediment samples were also obtained by means of a Van Veen grab, for determination of texture and organic-matter content. The association of environmental factors with species abundance was evaluated by Canonical Correspondence Analysis (α = 0.05). Forty-one species of Decapoda were used in the multivariate analysis. The analysis indicated that sediment texture (phi) and bottom temperature were the main factors correlated (p < 0.05) with the spatial and temporal abundance of the species. Considering the study region as faunal transition zone, including a mixture of species of both tropical and subantarctic origin, the species responded differently to environmental factors, mainly temperature. It is conceivable that the decapods adjust their distribution according to their intrinsic physiological limitations, possibly as a result of the available resources.
Keywords: especies bentonicas; crustaceos decapodos; fatores ambientais; selecao de habitat; benthic species; decapod crustaceans; environmental factors; habitat selection